2015
DOI: 10.4172/2157-7471.1000289
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Botanical Fungicides against Curvularia lunata at Molecular Levels

Abstract: Juniperus procera and Avicennia marina extracts were tested for their antifungal activity against Curvularia lunata isolated from rice (Oryza sativa L.). Eextracts were able to supress C. lunata at high concentration 3 mg/ml. J. procera extract retarted the growth C. lunata by 88.42% while A. marina extract was less effective (37.50%). Nucleic acids content of C. lunata was reduced by both plant extracts especially J. procera extract in a distinct reverse proportion relationship when compared with the untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Similarly, El-Baz et al (2016) recorded pH 6.5 as the best for silver nanoparticles biosynthesis. Lately, the antimicrobial activity of negatively charged oxygen compounds (pigments) had been reported as the bioactive compounds in the biological control (Abdel Ghany et al 2015). In the present study, the antimicrobial action of AgNPs has been associated with M. purpureus EG crude metabolite compounds chemical properties and their versatility such as deacetylation degree and molecular weight.…”
Section: Antimicrobial Activity Of Agnpsmentioning
confidence: 58%
See 1 more Smart Citation
“…Similarly, El-Baz et al (2016) recorded pH 6.5 as the best for silver nanoparticles biosynthesis. Lately, the antimicrobial activity of negatively charged oxygen compounds (pigments) had been reported as the bioactive compounds in the biological control (Abdel Ghany et al 2015). In the present study, the antimicrobial action of AgNPs has been associated with M. purpureus EG crude metabolite compounds chemical properties and their versatility such as deacetylation degree and molecular weight.…”
Section: Antimicrobial Activity Of Agnpsmentioning
confidence: 58%
“…These results disagree with the results by Talapragada et al (2017) that reported that the antimicrobial action of extract containing M. purpureus pigment had shown negative results against E. coli which may be attributed to the type of the media or tested strain. Abdel Ghany et al (2015) reported that culture filtrate of Monascus strain had antibacterial action against Bacillus spp. Other research finds that antimicrobial activity is significantly determined by cell growth conditions and culture medium compositions (Narsing et al 2017).…”
Section: Antimicrobial Activity Of Monascus Pigmentsmentioning
confidence: 99%
“…Some bioactive compounds produced by certain plants have fungicidal or fungi toxic activities because of their ability to inhibit the growth of fungi and their spores [5] and also have the ability to block the biosynthetic process of pathogenic metabolite [3]. Citronellal, linalool, and  and  pinenes produced by Cymbopogon inhibited fungal growth effectively [15].…”
Section: Table 3 the Inhibitory Effect Of Botanical Extracts Onmentioning
confidence: 99%
“…However, using synthetic fungicides for a long period created environmental problems and human health [2]. These negative effects can be overcome by using more environmentally friendly pesticides [3], such as plant extracts that contain fungicidal effects [4]. Plant-based fungicides could break down faster than synthetic chemical pesticides, so they do not accumulate for a long time in the environment [5].…”
Section: Introductionmentioning
confidence: 99%
“…These can be exploited in controlling the growth of fungi consequently inhibiting secondary metabolite production. The effect of plant extracts has been investigated on C. lunata depicting alteration in growth, sporulation, and secondary metabolite pathways ( Ghany TM et al, 2015 ). Many investigations resulted in the screening of a wide variety of plant species/bioactive compounds for their antimicrobial activities and have revealed structurally unique biologically active compounds ( Matasyoh et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%